2019
DOI: 10.24203/ajas.v7i5.5785
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Behaviour Towards Tetanus Toxoid Immunisation in South-South, Nigeria: Findings from Antenatal Clinic Attendees

Abstract: Tetanus infection has remained a major health problem in the third world countries despite the availability and accessibility of effective antibodies as vaccines. The knowledge of women about the diseases may affect their behavior with regards to prevention of the disease. This was a descriptive cross sectional study to assess the knowledge and behavior towards tetanus toxoid immunization by 252 antenatal clinic attendees in two health facilities Uyo metropolis. The majority of respondents had heard ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
4
2
0
Order By: Relevance
“…The overall awareness was adequate since (35.2% and 35%) of the women had a good and fair level of awareness respectively. These findings supported by other studies done in Iraq [10,13] and Nigeria [14,15], which displayed adequate awareness of mothers about tetanus infection and immunization. The finding of the study however contradicts with the findings of studies conducted in Saudi Arabia [16] and Egypt [17,18], which stated that the majority of women had poor knowledge on MNT and TTV.…”
Section: Discussionsupporting
confidence: 89%
“…The overall awareness was adequate since (35.2% and 35%) of the women had a good and fair level of awareness respectively. These findings supported by other studies done in Iraq [10,13] and Nigeria [14,15], which displayed adequate awareness of mothers about tetanus infection and immunization. The finding of the study however contradicts with the findings of studies conducted in Saudi Arabia [16] and Egypt [17,18], which stated that the majority of women had poor knowledge on MNT and TTV.…”
Section: Discussionsupporting
confidence: 89%
“…The overall awareness was adequate since (35.2% and 35%) of the women had a good and fair level of awareness respectively. These findings supported by other studies done in Iraq [10,13] and Nigeria [14,15], which displayed adequate awareness of mothers about tetanus infection and immunization. The finding of the study however contradicts with the findings of studies conducted in Saudi Arabia [16] and Egypt [17,18], which stated that the majority of women had poor knowledge on MNT and TTV.…”
Section: Discussionsupporting
confidence: 88%
“…Results of present study indicated a significant relationship between number of children and level of awareness. This evidence was observed by former studies carried out in Nigeria [15,19], which confirmed that the level of awareness was significantly associated with parity.…”
Section: Factors Influencing Woman's Awarenesssupporting
confidence: 84%
“…Generally, compared to women who have had previous pregnancies, first-time pregnant women are given health talks, and in some clinics, they are offered extra antenatal counselling sessions. Previous studies have reported on individual and community-level factors associated with uptake of TTCV in Nigeria among women with different categories of pregnancy and childbirth [ 11 , 15 , 16 ]. Although the population investigated in this study was limited to first-time mothers, we observed that some factors associated with the uptake of two doses of TTCV shared similarities with studies conducted among other categories of women in Nigeria [ 11 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported on individual and community-level factors associated with uptake of TTCV in Nigeria among women with different categories of pregnancy and childbirth [ 11 , 15 , 16 ]. Although the population investigated in this study was limited to first-time mothers, we observed that some factors associated with the uptake of two doses of TTCV shared similarities with studies conducted among other categories of women in Nigeria [ 11 , 15 ]. Two factors consistently associated with higher odds of having at least two doses of TTCV are a high number of antenatal visits and location in the Southern region of Nigeria.…”
Section: Discussionmentioning
confidence: 99%